2009 Global Hunger Index: The challenge of hunger - von Grebmer, Klaus; Nestorova, Bella; Quisumbing, Agnes R.; Fertziger, Rebecca; Fritschel, Heidi; Pandya-Lorch, Rajul; Yohannes, Yisehac (Welthungerhilfe, 2009)
The Global Hunger Index (GHI) shows that worldwide progress in reducing hunger remains slow. The 2009 global GHI has fallen by only one quarter from the 1990 GHI. Southeast Asia, the Near East and North Africa, and Latin America and the Caribbean have reduced hunger significantly since 1990, but the GHI remains distressingly high in South Asia, which has made progress since 1990, and in Sub-Saharan Africa, where progress has been marginal. Some countries achieved noteworthy progress in improving their GHI. Between the 1990 GHI and the 2009 GHI, Kuwait, Tunisia, Fiji, Malaysia, and Turkey had the largest percentage improvements. Angola, Ethiopia, Ghana, Nicaragua, and Vietnam saw the largest absolute improvements in their scores. Nonetheless, 29 countries have levels of hunger that are alarming or extremely alarming. The countries with the highest 2009 GHI scores are Burundi, Chad, the Democratic Republic of Congo, Eritrea, Ethiopia, and Sierra Leone. In most of the countries with high GHI scores, war and violent conflict have given rise to widespread poverty and food insecurity. Nearly all of the countries in which the GHI rose since 1990 are in Sub-Saharan Africa. The current food and financial crises, linked in complex ways, will both have implications for food security, financial and economic stability, and political security. The impacts will be greatest on the poor and hungry, and the countries with the highest levels of hunger are also among the most vulnerable to the global downturn. Although the poor and the hungry are in general hurt the most by the food and financial crises, the exact impacts at the household level differ widely. Policy responses to the food and financial crises must take these different impacts into account. Social protection strategies should be designed to mitigate the current shock for the most vulnerable, lay the foundation for sustainable recovery, and prevent negative impacts in the future. Nutrition interventions, such as school feeding programs and programs for early childhood and maternal nutrition, should be strengthened and expanded to ensure universal coverage. An important part of the solution to global hunger is reducing gender inequality. This report compares the 2009 GHI with the 2008 Global Gender Gap Index, which is made up of four subindices: economic participation, educational attainment, political empowerment, and health and survival. The evidence shows that higher levels of hunger are associated with lower literacy rates and access to education for women. High rates of hunger are also linked to health and survival inequalities between men and women. Reducing gender disparities in key areas, particularly in education and health, is thus essential to reduce levels of hunger.